2020
DOI: 10.1186/s12870-020-2294-9
|View full text |Cite
|
Sign up to set email alerts
|

Cotton roots are the major source of gossypol biosynthesis and accumulation

Abstract: Background: Gossypol is a specific secondary metabolite in Gossypium species. It not only plays a critical role in development and self-protection of cotton plants, but also can be used as important anti-cancer and male contraceptive compound. However, due to the toxicity of gossypol for human beings and monogastric animals, the consumption of cottonseeds was limited. To date, little is known about the gossypol metabolism in cotton plants. Results: In this study, we found that cotyledon was the primary source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 44 publications
5
28
1
Order By: Relevance
“…Comparing the expression profiles of gossypol genes in stem and root, we observed much higher expression in roots, indicating gossypol biosynthesis to mainly occur in the root (Figure 4 and Table S9); this conclusion is consistent with previous reports (Smith, 1961;Zhao et al, 2020).…”
Section: Gospgf Regulates a Set Of Genes Underlying Gland Formationsupporting
confidence: 92%
“…Comparing the expression profiles of gossypol genes in stem and root, we observed much higher expression in roots, indicating gossypol biosynthesis to mainly occur in the root (Figure 4 and Table S9); this conclusion is consistent with previous reports (Smith, 1961;Zhao et al, 2020).…”
Section: Gospgf Regulates a Set Of Genes Underlying Gland Formationsupporting
confidence: 92%
“…However, when rootstock and scion belong to different family the grafting was not successful. In the present study, none of the four grafting approaches was successful between G. hirsutum and Helianthus annuus , as previously reported 19 . Previous studies revealed that intra familial grafts are rarely compatible, and inter familial grafts are essentially always incompatible 27 .…”
Section: Resultssupporting
confidence: 74%
“…In cotton, grafting experiments have been conducted for different purposes including transfer of root-knot nematode resistance 11 , recovery of plants from in vitro culture 12 , transgenic recovery 13 , transfer of cytokinins and abscisic acid hormones 14 , transfer of Verticillium dahlia resistance 15 , identification of the role of shoot on premature leaf senescence induced by potassium nutrition 16 , increased cryotolerance 17 , and resistance to leaf curl disease 18 . In a study of grafting experiments, Zhoa et al 19 concluded that the major source of gossypol was root system in glanded and glandless cotton. However, our unpublished data does not confirm this finding instead; we found that gossypol is also synthesized from other tissues in cotton.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, since gossypol is an important component of cotton glands, genes associated with gossypol was also studied. We also performed qRT-PCR analysis on 6 key enzyme genes in the gossypol synthesis pathway [42]. In GhWRKY138-silenced leaves, the expression levels of 4 genes decreased and 2 genes increased conversely ( Fig.…”
Section: Resultsmentioning
confidence: 99%